Production, characterization, and antioxidant activity evaluation of Rheum Ribes L. extract-loaded PLA/PEG nanofibers - AYAZ SEYHAN, SERAP; BİLĞİÇ ALKAYA, DİLEK (My University, 2023)
© 2023 Marmara University Press.The use of natural compounds such as biocompatible and non-toxic plant extracts, without undesired side effects, in tissue engineering applications, is highly preferred compared to chemical drugs. In recent years, many studies have been carried out to produce nanofibrous materials produced by electrospinning of bioactive plant extracts. Electrospun nanofibers have very large surface area, controllable pore size, and tunable drug release profiles. Several biocompatible polymers with excellent biocompatibility and biodegradability including poly ethylene glycol (PEG) and poly-lactic acid (PLA) have been widely used for the synthesis of nanofibers using the electrospun technique. The ethanol-water extract of the root parts of the Rheum ribes L. plant has antioxidant, antimicrobial, and antiurease effects. In this study, the characterization and performance of electrospun Rheum ribes L.-loaded (20 mg, 40 mg, and 60 mg in 20mL) poly (lactic acid) (PLA) (8%, w/v) /Polyethylene glycol (PEG) (1%, w/v) /Tween 80 (3%, w/v) nanofibrous mats for skin tissue engineering were investigated. Morphological (SEM), molecular interaction (FT-IR), thermal analysis (DSC), antioxidant activity and physical analysis were carried out after the production process. According to the results obtained, Rheum ribes L.-loaded PLA/PEG nanofibers have smooth fiber morphology in fine structure without beads, proper tensile strength and antioxidant activity. Consequently, Rheum ribes L.-loaded nanofibrous mats are suitable for skin tissue engineering applications.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); antioxidant activity; Electrospinning; nanofibers; polylactic acid; rheum ribes L; tissue engineering